Sharp selective scattering of red, green, and blue light achieved via gain material’s loss compensation - Ye, Yiyang (2019)
Frequency-selective scattering of light can be achieved by metallic nanoparticle’s localized surface plasmon resonance (LSPR). And this property may find an application in a transparent projection screen: ideally, specially designed metallic nanoparticles dispersed in a transparent matrix only selectively scatter red, green and blue light and transmit the visible light of other colors. However, optical absorption and surface dispersion of a metallic nanoparticle, whose size is comparable or smaller than mean free path of electrons in the constituent material, degenerate the desired performance by broadening the resonance peak width (i.e., decreasing frequency-selectivity) and decreasing light scattering intensity. In this work, it is shown that the problem can be solved by introducing gain material. Numerical simulations are performed on nanostructures based on silver (Ag), gold (Au) or aluminium (Al) with or without gain material, to examine the effect of gain material and to search for suitable structures for sharp selective scattering of red, green and blue light. And it is found that introducing gain material greatly improves performance of the structures based on Ag or Au except the structures based on Al. The most suitable structures for sharp selective scattering of red, green and blue light are, respectively, found to be the core-shell structures of silica/Au (core/shell), silica/Ag and Ag/silica, all with gain material.